1999
DOI: 10.1116/1.590902
|View full text |Cite
|
Sign up to set email alerts
|

Gap-filling property of Cu film by chemical vapor deposition

Abstract: Correlation between the early stage of copper metal organic chemical vapor deposition and the material properties of thin filmThe gap-filling property of Cu deposited by chemical vapor deposition was investigated in 1/4-m-wide trenches and 1/4-m-diam holes. Attention was paid to the influences on the gap-filling property of both substrate temperature and partial pressure of the source gas. At a low deposition temperature of 180°C, Cu could completely fill a hole with an aspect ratio of 7. A high deposition rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…A current method widely used for copper deposition is electroplating, which requires a copper seed layer (work as a cathode) formed with physical vapor deposition. Also, various kinds of chemical vapor deposition (CVD) techniques have been studied for conformal copper deposition over the past decade in order to replace the electroplating with the CVD, which is favorably used in the semiconductor industry. Although the recent CVD techniques enable us to make a conformal copper film at a rapid growth rate and fill small features with no voids and seams, adhesions of copper films on barrier layers such as TiN, TaN, and Ta are poor in most of the techniques . High deposition temperature (>200 °C) is another drawback of this technique.…”
Section: Introductionmentioning
confidence: 99%
“…A current method widely used for copper deposition is electroplating, which requires a copper seed layer (work as a cathode) formed with physical vapor deposition. Also, various kinds of chemical vapor deposition (CVD) techniques have been studied for conformal copper deposition over the past decade in order to replace the electroplating with the CVD, which is favorably used in the semiconductor industry. Although the recent CVD techniques enable us to make a conformal copper film at a rapid growth rate and fill small features with no voids and seams, adhesions of copper films on barrier layers such as TiN, TaN, and Ta are poor in most of the techniques . High deposition temperature (>200 °C) is another drawback of this technique.…”
Section: Introductionmentioning
confidence: 99%
“…This result is similar to the previous results. 17,18) Burke et al 18) reported that the conformality was directly proportional to the precursor flow rate. This is because the increase in precursor flow leads to a higher probability of adsorption/ re-emission within the via or trench structure.…”
Section: Deposition Characteristicsmentioning
confidence: 98%
“…The enhancement of precursor concentration can be achieved by increasing the precursor partial pressure in the reaction zone by the increase of the precursor flow while keeping all other process parameters fixed. The partial pressure of precursor (P precursor ) is defined as follows: 17,18) …”
Section: Deposition Characteristicsmentioning
confidence: 99%
“…[12][13][14] Furthermore, in several crystallographic and morphological studies, attempts have been made to correlate the transport properties of pentacene thin films with morphology and molecular orientation. [15,16] However, although the voids that act as traps or barriers to hopping transport at the interface between the active layer and the insulator substrate are usually formed during the pentacene deposition process, [17] little is known about the relationship between the voids at the interface and carrier transport. [9] Here, we report the effect of voids at the interface between the pentacene film and the dielectric layer on the performance of pentacene transistors, and suggest a methodology for filling such voids and improving the interconnectivity in the channels of pentacene thin films by controlling the pentacene sublimation rate.…”
Section: Introductionmentioning
confidence: 99%